Sensory Nudges: The Influences of Environmental Contexts on Consumers' Sensory Perception, Emotional Responses, and Behaviors toward Food and Beverages - Seo, Han-Seok (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Cake products with highly acceptable flavor and mouthfeel are not always successful in the marketplace. Sales of identical cake products sold in two different bakery shops often differ. Patrons' choices of specific cake items differ depending on menu designs at restaurants. Such examples suggest that consumer behavior related to eating, preparing, or purchasing foods and beverages is typically complex, dynamic, and sensitive to environmental cues surrounding them. The nine original research articles and two systematic review articles addressed in this book provide recent informative and insightful findings on how sensory cues related to eating/drinking environmental contexts can serve as "sensory nudges" that induce healthy eating and drinking along with consumer satisfaction.